Relationship Between Body Image and Psychology Student Confidence at Muhammadiyah University of Gresik - Risa Aulia; Ima Fitri Sholichah (Raudhatun Najah Publisher, 2022)
Confidence is an individual's belief in the abilities they have. This study aims to determine the relationship between body image and student self-confidence. The subjects needed in the research were psychology students at the Muhammadiyah University of Gresik who had fulfilled the research requirements. The data collection tools used in this study were the body image and self-confidence scales—data analysis method using Pearson's Product Moment Correlation Technique. The results showed that the correlation was 0.618 with sig 0.000 (p <0.05), meaning that there was a positive and significant relationship between body image and the self-confidence of students at Muhammadiyah University of Gresik, Faculty of Psychology.